Model of Anti-Covid-19 Pharmacon - dimri, Mayank; Rajwar, Virbal Singh; Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2020)
COVID-19 pandemic opens multiple opportunities for innovations in the drug –design. Combinational therapeutics and renewal of orphan drugs as antivirals. The drugs of pharmacological diversity may be tomorrow of viral replication blockers. A model of polyactive pharmacon is suggested for hybridizing structural moieties of virucidal relevance.